ACHIEVEMENT OF SMP BATIK SURAKARTA STUDENTS IN ACADEMIC YEAR 2020 – 2021 - Widayati, Wening; Istiatin, Istiatin; Sudarwati, Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Student Achievement of SMP Batik Surakarta Academic Year 2020 – 2021, Post Graduate Management Study Program, Batik Islamic University Surakarta, 2021 Student achievement is closely related to teacher competence, learning methods, and school infrastructure accompanied by student learning motivation, so it is necessary to conduct research related to it. This study aims to analyze the influence of competencies, teachers of learning methods, infrastructure, and motivation of students on student achievement at SMP Batik Surakarta Academic Year 2020 – 2021. The research method uses multiple linear regression analysis quantifications. The research population of grade VIII students as many as 244 students of sampling techniques purposive sampling obtained a sample of 80 students ranked in the top ten schools. The results of researching teacher competence, learning methods, school infrastructure effect while the motivation of students' learning does not affect the learning quality of students of SMP Batik Surakarta Academic Year 2020 – 2021. Keywords: teacher competence, learning methods, infrastructure, learning motivation, student achievement.